Muscle fibre type, size and satellite cell pool in male volleyball players - Balasas, Dimitrios G.; Mandroukas, Athanasios; Michailidis, Yiannis; Drikos, Sotirios; Sotiropoulos, Κοnstantinos; Christoulas, Kosmas; Metaxas, Thomas I.; Bampouras, Theodoros M. (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Longitudinal volleyball training stimuli can cause an increase in muscle strength that is brought about by neurological and morphological adaptations, such as changes in muscle fibre composition percentage and cross-sectional area (CSA). Aim of Study. The aim of this study was to examine the biological adaptations of volleyball-players in terms of muscle fiber type composition, cross-sectional area, myonuclei and satellite cell pool in comparison to physically active controls. Material and Methods. Ten professional volleyball-players (VG) and five physically active-persons (CG) participated in this study. Muscle biopsies were obtained from the vastus-lateralis of the dominant leg. Results. Immunohistochemical analysis revealed that although MHC I and MHC IIC muscle fibre distribution was not different between the groups, MHC IIX and MHC IIAX were totally absent in VG and appeared only in the CG. The cross-sectional area revealed a slightly different pattern as both MHC I and IIA were larger for the volleyball players. In accordance, MHC II myonuclei number was moderately larger in the volleyball players, while the satellite cells and their ratio to number of fibres had a large and very large difference, respectively. Conclusions. In conclusion, our study reveals that volleyball training-induced hypertrophy for both type I and II muscle fibres in the vastus lateralis of volleyball players and resulted in a specific shift in muscle fibres containing MHC II isoforms. This hypertrophy of the muscle fibres is associated with an increase in the myonuclear number and satellite cells.
Keywords: volleyball; muscle fibre; cross-sectional area; satellite cells